2012
DOI: 10.1111/cas.12002
|View full text |Cite
|
Sign up to set email alerts
|

Romidepsin (FK228) and its analogs directly inhibit phosphatidylinositol 3‐kinase activity and potently induce apoptosis as histone deacetylase/phosphatidylinositol 3‐kinase dual inhibitors

Abstract: Activation of phosphatidylinositol 3-kinase (PI3K) signaling is involved in carcinogenesis and cancer progression. The PI3K inhibitors are considered candidate drugs for cancer treatment. Here, we describe a drug screening system for novel PI3K inhibitors using Saccharomyces cerevisiae strains with deleterious mutations in the ATP-binding cassette transporter genes, because wild-type S. cerevisiae uses drug efflux pumps for reducing intracellular drug concentrations. By screening the chemical library of the Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 26 publications
(32 reference statements)
1
48
0
Order By: Relevance
“…It was previously reported that the HDAC inhibitor romidepsin (FK228) and its analogues inhibit phosphatidylinositol 3 kinase activity leading to increased effects on cancer cell death. 41 Furthermore, several kinases inhibited by these compounds interact with proteins either associated with histone acetylation or deacetylation or with regulators of this activity ( Figure 5). Indeed, SRC and AKT interact directly with HDAC3, while PRK1 interacts with both HDAC5 and HDAC6.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was previously reported that the HDAC inhibitor romidepsin (FK228) and its analogues inhibit phosphatidylinositol 3 kinase activity leading to increased effects on cancer cell death. 41 Furthermore, several kinases inhibited by these compounds interact with proteins either associated with histone acetylation or deacetylation or with regulators of this activity ( Figure 5). Indeed, SRC and AKT interact directly with HDAC3, while PRK1 interacts with both HDAC5 and HDAC6.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Third, the drugs could have additional offtarget effects. For instance, romidepsin has been reported to inhibit PI3K signaling (42). In fact, some differences between the effects of romidepsin and givinostat on UCCs could be explained by off-target activities.…”
Section: Discussionmentioning
confidence: 99%
“…CUDC-907 is another dual-acting agent developed by the same research group to inhibit both HDACs and phosphoinositide 3-kinase (PI3K) (Qian et al 2012) and its clinical trials are underway for the treatment of lymphoma and multiple myeloma as well as advanced/relapsed solid tumors. Romidepsin (FK228, depsipeptide) is a potent Class I histone deacetylase inhibitor that has FDA approval for the treatment of cutaneous and peripheral T-cell lymphomas, and recent research demonstrated that FK228 and its analogs (FK-A5 and FK-A11) act as HDACs and PI3K dual inhibitors (Saijo et al 2012; Saijo et al 2015). …”
Section: Anticancer Effect Of Hdac Inhibitorsmentioning
confidence: 99%